PERAN UNITED NATIONS WOMEN (UN WOMEN) DALAM MERESPONS KEKERASAN BERBASIS GENDER TERHADAP PEREMPUAN SELAMA PANDEMI COVID-19 DI AFRIKA SELATAN - Ananda, Septia Laisya; Takwa, Tuah Kalti (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2025)
Gender-Based Violence (GBV) against women is a phenomenon that has occurred and attracted quite a lot of public attention in South Africa. However, with the presence of Covid-19, cases of Gender-Based Violence against women have increased due to regional quarantines, which have limited community mobility. On the other hand, during the lockdown policy, several homes in South Africa have become places of violence for women and girls who are trapped with violent family members and cannot escape from danger. This study aims to analyze the role of United Nations Women (UN Women) in responding to Gender-Based Violence against women during the Covid-19 pandemic in South Africa. In this study, the method used is a qualitative method. with the writing model used in this study is a descriptive model. This study uses secondary data collection techniques with sources being literature, articles, journals and websites on the internet related to this study. The results of this study show that UN Women plays an important role as an independent actor in responding to GBV in South Africa. This can be shown through the capacity of this organization to act outside of direct state instructions and in determining the global agenda and norms related to gender equality and the protection of women through public social campaigns, Protection for GBV survivors, advocacy and policy reform and women's economic empowerment. Keywords: UN Women, International Organizations, Gender-Based Violence, Covid-19 Pandemic, South Africa.